Penerapan Niche Marketing melalui Pendekatan Social Media Marketing terhadap Situs Wisata Sejarah Punden dan Sumur Windu - Joshua Tiento; Daffa’ul Hanif Muhibin; Raden Johnny Hadi Raharjo; Nanik Haryana4 (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The historical tourist sites of Punden and Sumur Windu, which are located in Gadel Village, Karangpoh Village, Surabaya City, are considered to need to be improved in a more massive development in order to increase the potential of historic tourism in the era of modern technological progress as it is today. The existence of historical culture that is still developing and surviving in the community opens up opportunities to increase tourism potential, especially historical sites in Gadel Village. The strategy for utilizing niche marketing through a social media marketing approach on social media can later be a solution so that the historical tourist sites of Punden and Sumur Windu can be marketed to the wider community, especially among connoisseurs of traditional art, culture, and history. This marketing technique is supported by the rapid development of the social media industry.